Evaluation of Source and Sink Capacity of New Cowpea Varieties - Saidah, Faza Yasmin; Purnamawati, Heni; Lubis, Iskandar (Journal of Tropical Crop Science, 2023)
Cowpea (Vigna unguiculata (L.) Walp) is a perennial species originating from sub-Saharan Africa. Cowpea has long been cultivated in Indonesia and is classified as a species tolerant of drought and acid soil. Cowpea shows its adaptation to acidic soil (pH = 4.83) by being able to produce 50% to 60% of the seed weight under optimum conditions. This enhances the potential of cowpea to be used and developed as one of the current food options. This research was carried out to optimise of cowpea productivity by studying the relationship between the source and sink of cowpea. This research was conducted from December 2020 to March 2021 at the Cikabayan experimental station, Bogor Agricultural University. The experiment was set up in a completely randomized block design. Four cowpea varieties were evaluated, “Albina”, “Arghavan”, and “Uno”. The measured parameters consisted of photosynthesis rate, stomatal conductance, plant growth rate, the net assimilation rate of the number of pods, pod weight, number of seeds per pod, dry seed weight, the weight of 100-seeds, and productivity. The cowpea varieties did not show significant differences in the rate of photosynthesis, stomatal conductance, plant growth rate, and net assimilation rate. Photosynthesis rate in the three cowpea varieties ranged from 29.20 to 31.77 mol. m⁻².s⁻1 at 50% flowering, and from 17.01 to 19.79 mol.m⁻².s⁻1 at the first harvest. The three cowpea varieties in this study showed no differences in their source-sink capacity and productivity.